Applications Aspects of the Diffusion of Slow Electrons in the Ionospheric Gases - Baghdad Science Journal (مجلة بغداد للعلوم)
The paper presents the results of precise of the calculations of the diffusion of slow electrons in ionospheric gases, such as, (Argon – Hydrogen mixture, pure Nitrogen and Argon – Helium – Nitrogen) in the presence of a uniform electric field and temperature 300 Kelvin. Such calculations lead to the value Townsend's energy coefficient (KT) as a function of E/P (electric field strength/gas pressure), electric field (E), electric drift velocity (Vd), momentum transfer collision frequency ( ), energy exchange collision frequency ( ) and characteristic energy (D/?). The following physical quantities are deduced as function s E/P: mean free path of the electrons at unit pressure, mean energy lost by an electron per collision, mean velocity of agitation and the collisional cross-section of the molecules. The results are presented graphically and in tabular form. This results appeared a good agreement with the experimental data.